“Anxiscape”: an adventure in conquering anxiety via Game-Based Learning (GBL) for students - Zulhemay, Mohd Nabil; Sulan, Onesimus (College of Computing, Informatics, and Mathematics, 2025)
On Anxiety is a pervasive mental health issue that significantly impacts individuals' physical, mental, and emotional well-being. Despite the crucial importance of mental health education, the young generation, especially students are facing difficulty in acquiring information about anxiety from sources or tools which appeal to them. As an example, the scarcity or the absence of a usability of Game-Based Learning (GBL) application in providing the abovementioned information. This is a possible challenge leading to a lack of enjoyment in learning about mental health education. Recognizing the need for a more engaging approach, this study aims to create a GBL application designed to disseminate information to students about anxiety. The project used the Game Development Life Cycle (GDLC) methodology. The evaluation was conducted using the instrument from the E-Game Flow Model and Heuristic Evaluation with a 5-point Likert scale. The results show a remarkable overall mean of 90%, indicating that most users have a positive enjoyment with the application. Moreover, 85.4% of the overall mean, indicating that most user have positive result on the usability of the application. This project has an impact on students by making it easier for them to know about Mental Health Education on topic anxiety via Game-Based Learning. Further enhancements in this project have been identified for future improvement, including explore ways to balance the depth and complexity of educational content with user engagement in serious games and develop ways to optimize the game's performance across different devices and internet conditions